HIS LAST BOW : An Epilogue of Sherlock Holmes - Doyle, Arthur Conan, Sir, 1859-1930 (Kuala Lumpur : Popular Book Co. (M) Sdn. Bhd., 2024)
"His Last Bow: An Epilogue of Sherlock Holmes," written by Sir Arthur Conan Doyle is the very last of the 56 published Sherlock Holmes stories. In this account we see Holmes depart from his typical crime-solving role, instead acting as a spy in an effort to foil a German spy's attempt to smuggle state secrets out of Great Britain. Although he ultimately wins the day, this is not your typical Sherlock Holmes tale.
Keywords: English fiction; Detective and mystery stories, English